Analysis of Mineral and Vitamin Content in Sweet Potato Leaves and Their Potential Role in Hemoglobin Formation - Yayuk Nuryanti; Hosiana Loisa Sombuk; Achmad Taher (Buletin Penelitian Kesehatan, 2025)
Background: Sweet potato leaves are widely consumed in Indonesia and have been traditionally used to help overcome anemia due to their mineral and vitamin content. This study aimed to analyze the mineral and vitamin C content of green and red sweet potato leaves and to assess their potential role in supporting hemoglobin formation. Methods: This type of research is descriptive by explaining the results of laboratory tests on water extracts and red and green sweet potato leaves. Samples of water extract from 10 red sweet potato leaves and 10 green sweet potato leaves. Meanwhile, for the leaf extract, each leaf was air-dried for 1 week and then placed in an oven at 1050C for 3 days until the weight remained constant. To analyze the minerals, samples were tested using a SHIMADZU Type AA-7800 Atomic Absorption Spectrophotometer (AAS). Vitamin C analysis was performed using the titration method. Results: The results of the study were obtained from the green leaf extract Fe 56.36 gr, Ca 1052.2 gr, Mg 3.3 gr. Red leaves Fe 55.46 gr, Ca 285.9 gr, and Mg 32.46 gr. The content of boiled water extract for 10 minutes Fe 0.15 mg/l, Ca 0.54 mg/l, Mg 1.9 mg/l. Pink leaves Fe 0.08 mg/l, Ca 0.745 mg/l, Mg 1.88 mg/l. Dark red leaves Fe 0.11 mg/l, Ca 0.95 mg/l, Mg 1.92 mg/l. Water extract with added sugar on green leaves Fe 0.04 mg/l, Ca 0.84 mg/l, and Mg 1.89 mg/l. Red leaves Fe 0.08 mg/l, Ca 1.27 mg/l, and Mg 1.91 mg/l. The vitamin C content of green sweet potato leaves is higher than that of red sweet potato leaves, indicating its potential as a more effective food source to increase hemoglobin levels and overcome anemia. Conclusion: Sweet potato leaves contain important nutrients, based on the results of extracts from green sweet potato leaves containing higher concentrations of minerals and vitamin C.